2005
DOI: 10.1088/0305-4470/38/31/010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum anomalies for generalized Euclidean Taub–NUT metrics

Abstract: The gravitational anomalies are investigated for generalized Euclidean Taub-NUT metrics which admit hidden symmetries analogous to the Runge-Lenz vector of the Kepler-type problem. In order to evaluate the axial anomalies, the index of the Dirac operator for these metrics with the APS boundary condition is computed. The role of the Killing-Yano tensors is discussed for these two types of quantum anomalies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In the case of the generalized Taub-NUT spaces the S-K tensors involved in the Runge-Lenz vector cannot be expressed as a product of K-Y tensors. The non-existence of the K-Y tensors on generalized Taub-NUT metrics leads to gravitational quantum anomalies proportional to a contraction of the S-K tensor with the Ricci tensor [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the generalized Taub-NUT spaces the S-K tensors involved in the Runge-Lenz vector cannot be expressed as a product of K-Y tensors. The non-existence of the K-Y tensors on generalized Taub-NUT metrics leads to gravitational quantum anomalies proportional to a contraction of the S-K tensor with the Ricci tensor [13].…”
Section: Introductionmentioning
confidence: 99%
“…We conjecture that it equals 0 and hence, unlike on annular domain or balls, the axial anomaly is never present. Our guess is motivated by heuristically increasing the radius of a ball to infinity, and arguing that by [13], the index stabilizes at 0 for large radii. Such an argument is of course incomplete, and even dangerous in the light of the fact that the Dirac operator is not Fredholm.…”
Section: Introductionmentioning
confidence: 99%
“…In [22] we computed the index of the Dirac operator on annular domains and on disk, with the non-local APS boundary condition. For the generalized Taub-NUT metrics [19,20,21], we found that the index is a number-theoretic quantity which depends on the metrics.…”
Section: Index Formulas and Axial Anomaliesmentioning
confidence: 99%
“…We mentioned in [22] some open problems in connection with unbounded domains. The paper [35] brings new results in this direction.…”
Section: Index Formulas and Axial Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation